Kolaborasi Pentahelix pada Program Satu Organisasi Perangkat Daerah (OPD) Satu Desa Binaan dalam Pengentasan Kemiskinan Ekstrem di Provinsi Maluku: Studi pada Enam Desa Prioritas di Kabupaten Seram Bagian Timur - Rusmiati Mahu; Alfitri Alfitri; Katriza Imania (Universitas Muhammadiyah Ponorogo, 2026)
Extreme poverty is a multidimensional issue that demands a collaborative, cross-sectoral approach. Through the One OPD, One Fostered Village program, the Maluku Provincial Government aims to facilitate the involvement of five key pentahelix actors—government, private sector, academia, community, and mass media—to accelerate poverty alleviation in priority villages. This study investigates the dynamics of collaboration, the forms of collaborative actions, and the impacts of the pentahelix model in the implementation of the program. Employing a qualitative approach with a focused case study in six priority villages in East Seram Regency, data were gathered through in-depth interviews, participatory observations, and document analysis. Thematic analysis was conducted using the collaboration framework developed. The study offers practical recommendations, including strengthening cross-sectoral coordination, expanding the roles of collaborative actors, developing a sustainability roadmap, and improving policy frameworks to enhance the program’s long-term effectiveness and sustainability. Keyword: Pentahelix Collaboration; Extreme Poverty; Alleviation; One Opd One Fostered Village, Maluku;